Seabird stress and breeding: Endocrine and hematological stress biomarkers differ between gray‐faced petrel (Pterodroma gouldi) colonies. Issue 4 (15th February 2022) - Whitehead, Edin A.; Russell, James C.; Hickey, Anthony J.; Taylor, Graeme A.; O'Reilly, Katie M.; Della Penna, Alice; Dunphy, Brendon J.
Abstract: Seabird breeding success is known to reflect oceanic conditions. Gray‐faced petrels ( Pterodroma gouldi ) breeding on the east coast of Auckland, New Zealand, exhibit poor reproductive success and slow chick development compared to west coast conspecifics. This study mapped changes in physiological traits (corticosterone [CORT] and hematological parameters) indicative of sublethal stress in this Procellariiform species between the west coast (Ihumoana) and east coast (Hāwere) island colonies. We found adult gray‐faced petrels on the east coast to be lighter and, unlike west coast birds, exhibited an attenuation of response CORT levels between incubation and chick‐rearing phases. Such responses were also reflected in east coast chicks that were lighter and had higher feather CORT titers than west coast chicks. Measures of adult hematology and plasma biochemistry revealed significantly lower glucose levels in east coast birds and indicated that chick rearing is the most stressful phase of breeding for this species Combined; these results suggest that east coast birds are under greater nutritional stress and that parents appear to transfer the costs of poor foraging to their chicks to preserve their own condition, consequently increasing chick developmental stress. Our results suggest that any long‐term decrease in ocean conditions and/or climatic shifts would be more acutely felt by east coast chicks and potentially their parents, resulting in years of poor breeding success rates on a local scale. Abstract : Comparison of key physiological changes in gray‐faced petrel ( Pterodroma gouldi ) adults and chick at west and east coast breeding colonies within northern New Zealand. Research Highlights: Stresses incurred across breeding season compared in a key apex predator. Stress of breeding only evident in adults at inferior colonies during the chick‐rearing phase. Such stresses (high‐stress hormones) are reflected in chick physiology, underpinning poor chick growth and performance.